Detection of deltamethrin resistance in eggs and larva of Rhipicephalus (Boophilus) microplus - SHARMA, NEELU; SINGH, VEER; SHYMA, K P; SOLANKI, VIKRAM; GUPTA, JAY PRAKASH (The Indian Journal of Animal Sciences, 2017)
Rhipicephalus (Boophilus) microplus is the most common tick species in India infesting cattle and buffaloes and cause significant economic losses to dairy and leather industries by adversely affecting the milk production and quality of hides. Egg hatch assay and larval packet test were used to evaluate the comparative acaricidal efficacy of the market formulations of deltamethrin, cypermethrin and amitraz on eggs and larval stages of R. (B.) microplus. The regression graphs of probit hatchability, % inhibition of hatching (IH) of eggs and probit mortality were plotted against log concentrations of various acaricides. The results revealed that cypermethrin and amitraz were effective and produced complete inhibition of hatching. LC95 values of cypermethrin and amitraz calculated by larval packet test were estimated to be 244.91 ppm and 369.83 ppm, respectively. On the other hand, deltamethrin failed to completely inhibit the hatching. LC95 values by egg hatch assay and larval packet test were estimated to be 42.27 ppm and 39.36 ppm, respectively. The data on field status of acaricide resistance from the area with diversified animal genetic resources will be helpful to adopt suitable strategy to overcome the process of development of resistance in ticks.